Smashing statues : the rise and fall of America's public monuments - Thompson, Erin L. (W. W. Norton & Company, 2022)
"A leading expert's exploration of the past, present, and future of public monuments in America. An urgent and fractious national debate over public monuments has erupted in America. Some people risk imprisonment to tear down long-ignored hunks of marble; others form armed patrols to defend them. Why do we care so much about statues? And who gets to decide which ones should stay up and which should come down? Erin L. Thompson, the country's leading expert in the tangled aesthetic, legal, political, and social issues involved in such battles brings much-needed clarity in Smashing Statues. She traces the turbulent history of American monuments and its abundant ironies, starting with the enslaved man who helped make the statue of Freedom atop the US Capitol, and explores the surprising motivations behind such contemporary flashpoints as the toppling of a statue of Columbus at the Minnesota State Capitol. Written with great verve and thoroughly researched, Smashing Statues gives readers the context they need to consider the fundamental question: Whose voices must be heard and whose pain must remain private?"--